Ant Colony Optimization algorithm for robot path planning - Brand, M; Masuda, M; Wehner, N; Xiao-Hua Yu (2010 International Conference On Computer Design and Applications, 2010)
Path planning is an essential task for the navigation and motion control of autonomous robot manipulators. This NP-complete problem is difficult to solve, especially in a dynamic environment where the optimal path needs to be rerouted in real-time when a new obstacle appears. The ACO (Ant Colony Optimization) algorithm is an optimization technique based on swarm intelligence. This paper investigates the application of ACO to robot path planning in a dynamic environment. Two different pheromone re-initialization schemes are compared and computer simulation results are presented.